Ni / MgO Bifunctional Catalyst for Condensation and Furfural Hydrogenation Reactions in One Stage Produce Alkana C8-C13 Derived Compounds - Siti Mariyah Ulfa; Indah Nur Pramesti (Natural B, Journal of Health and Environmental Sciences, 2015)
Ni/MgO catalyst has been designed as bifunctional catalyst for condensation reaction of furfural and acetone followed by hydrogenation reaction to produce C8-C13 alkane derivatives in one step reaction. Ni/MgO catalyst was prepared by wet impregnation methods using Ni(NO3)2.6H2O and MgO as supporting material. The charcterization by X-ray diffraction (XRD) showed the characteristic of Ni on 2q = 44,27o; 51,59o and 75,89o. Isoterm adsorpsi using N2 gas gave the decreasing surface area of MgO and forming microporous structure. The activity test of the catalyst was carried out using furfural and acetone (1:1) in autoclave bath system, heated at 100-180oC for 7-8 hours in the presence of water. Ni/MgO catalyst showed the good activity when hydrogenation reaction performed at 150oC lead to the conversion of alkane derivatives in 95.69%. Characterization of the product by GC-MS showed the formation of 4-(2-furanyl)-2-butanone; 1,5-di(2-furanyl)-3-pentanone and 1,5-di(2-furanyl)-3-(1-pentenone) from reduction of C=C alkene of furfurylidene acetone.